Combining high dose therapy, bilateral motor priming, and vagus nerve stimulation to treat the hemiparetic upper limb in chronic stroke survivors: a perspective on enhancing recovery - King, Erin C.; Pedi, Elizabeth; Stoykov, Mary Ellen; Corcos, Daniel M.; Urday, Sebastian (Frontiers in Neurology, 2023)
Stroke is a leading cause of disability worldwide and upper limb hemiparesis is the most common post-stroke disability. Recent studies suggest that clinically significant motor recovery is possible in chronic stroke survivors with severe impairment of the upper limb. Three promising strategies that have been investigated are 1) high dose rehabilitation therapy 2) bilateral motor priming and 3) vagus nerve stimulation. We propose that the future of effective and efficient upper limb rehabilitation will likely require a combination of these approaches.